Functionalized-AgNPs for Long-Term Stability and Its Applicability in the Detection of Manganese Ions - Van-Tuan Hoang; Mai Mai; Le Thi Tam; Ngoc Phan Vu; Nguyen Tien Khi; Phuong Dinh Tam; Tran Quang Huy; Anh-Tuan Le; Ngo Xuan Dinh; Vinh-Hoang Tran (Advances in Polymer Technology)
In this study, silver nanoparticles (AgNPs) were functionalized by various molecules, including sodium borohydride (NaBH4), polyhexamethylene biguanide hydrochloride (PHMB), and Tween 80 to investigate the long-term stabilization of AgNPs in an aqueous dispersion. PHMB-functionalized silver nanoparticles (AgNPs/PHMB) exhibited better stability than others and could be stored at ambient temperature for at least 180 days. In addition to creating stabilization based on the electrostatic repulsion, the use of PHMB helped to increase the degree of stability of the colloidal AgNPs for a long time owing to strong interactions between Ag atoms on AgNPs with nitrogen (N) positions in PHMB molecules. The formed bond led to improving maintenance ability of the electrostatic repulsion layer among independent nanoparticles. The applicability of the as-prepared AgNPs/PHMB was also examined for Mn2+ detection via a colorimetric approach. The calibration curve was found to be linear over the range of 0–100 mM with a correlation coefficient of 0.97. The amine groups of PHMB brought out a cooperative effect to form of ion-templated chelation with Mn2+, which caused the aggregation of AgNPs/PHMB. This suggested that the AgNPs/PHMB could be used as a potential probe in the detection of Mn2+ ions. More importantly, the long-term stability of AgNPs/PHMB paved a great promising path to provide many further solutions for the producer in practical applications.